UPAYA PEMERINTA DESA DALAM PEMEKARAN DUSUN DI DESA MUARA TAKUS TAHUN 2015 - Fauzy Ari Hidayat; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The expansion of the Government area is a strategic step taken by the Government to improve the quality of the implementation of Government task both in the framework of service, empowerment of development to the fair and prosperous. Regional expansion efforts are seen as a breakhtrough to accelerate deveopment through improving the quality and ease of obtaining services for the community. Law No. 23 of 2014 on regional Government Article 32 Paragraph 1 “ The expansion of regions as referred to in Article 32 Paragraph 1 shall be in the form of (a) the split of provincial or regency/municipal regions to become two or more new areas. Matching or splitting from one region to two or more regions”. Village Government Muara Takus seeks to split the existing hamlet in the village, it is triggered by the increasing, and the area of the estuary village is also widened so that the administrative services carried out by the RT does not run optimally and the RT power range is not up to the scope of the RT because of the distance of the population far apart.The implementation of the division of village in the village Muara Takus has many inhibiting factors such as, firstly, the lack of village budget funds which is the most important part to make the expansion of a region, due to the succes of an expansion of the existence of budget funds to conduct the expansion of the region. Secondly, the lack of the infrastructure in the village, especially in the hamlet area which is an important part in the community, due to its nature as container or the absolute requirement to bring the society to be prosperous. Third, the absence of support from the local Government of Kampar district, any division of a region should get support from the local Government then the procces of expansion of the region will be done well.Keywords: Government, Village, Regional expansion, Hamlet